2016
DOI: 10.1080/09853111.2015.1121802
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of climate change on groundwater recharge in Küçük Menderes River Basin in Western Turkey

Abstract: Groundwater is an important component of the global freshwater supply and is affected by climate. There is a strong need to understand and evaluate the impacts of climate change over the long term, in order to better plan and manage precious groundwater resources. Turkey, located in Mediterranean basin, is threatened by climate change. The purpose of this study was, through a quantitative overview, to determine the impacts of climate change on the groundwater recharge rates in Küçük Menderes River Basin in wes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 21 publications
0
10
0
4
Order By: Relevance
“…This represents 1.56×10 6 m 3 •yr −1 •km −1 suggesting a still low "natural" SGD value. A recharge ratio of between 23 and 52% (average 35%) for karstified carbonates [Allocca et al, 2014, Arfib and Charlier, 2016, Baudement et al, 2017, Martos-Rosillo et al, 2015, Polemio, 2016, Zagana et al, 2007, and between 10 and 21% (average 16%) for detritic aquifer formations [Séraphin et al, 2016, Yagbasan, 2016, Zagana et al, 2007 were reported in the north Mediterranean area (Spain to Turkey). Given that karstic aquifers represent almost 20% of the coastal areas in Mediterranean Europe [Goldscheider et al, 2020], an average value of about 20% for the recharge ratio, therefore tenfold higher than in the southern part of the Mediterranean domain (2 to 3%), can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This represents 1.56×10 6 m 3 •yr −1 •km −1 suggesting a still low "natural" SGD value. A recharge ratio of between 23 and 52% (average 35%) for karstified carbonates [Allocca et al, 2014, Arfib and Charlier, 2016, Baudement et al, 2017, Martos-Rosillo et al, 2015, Polemio, 2016, Zagana et al, 2007, and between 10 and 21% (average 16%) for detritic aquifer formations [Séraphin et al, 2016, Yagbasan, 2016, Zagana et al, 2007 were reported in the north Mediterranean area (Spain to Turkey). Given that karstic aquifers represent almost 20% of the coastal areas in Mediterranean Europe [Goldscheider et al, 2020], an average value of about 20% for the recharge ratio, therefore tenfold higher than in the southern part of the Mediterranean domain (2 to 3%), can be considered.…”
Section: Discussionmentioning
confidence: 99%
“…This change includes a decrease in low and moderate precipitation causing droughts over India. Precipitation affects ground water recharge and thus has a significant impact on ground water level (Yagbasan 2016). Ground water recharge has been calculated using technique described in methodology section.…”
Section: Climate Change Impact On Ground Water Levelmentioning
confidence: 99%
“…The mean annual precipitation calculated for the study area is 640 mm. Surface water quality class is not proper for many purposes in the region and main reason is uncontrolled industrial and agricultural discharges [7,8].…”
Section: Study Areamentioning
confidence: 99%